Ideas of possession interdisciplinary and transcultural perspectives - Bauer, Nicole 1980-; Doole, J. Andrew 1984- (Oxford University Press, 2024)
"The characteristics of possession are numerous and vary between different socio-cultural and historical contexts. Different ideas of possession can be observed within different cultural and social contexts both past and present. This makes defining possession all the more difficult. Various approaches to "ideas of possession" in different academic disciplines and in different cultural contexts allow the discourse(s) to benefit from insights that would otherwise remain confined to the society under discussion or the field that determines the method of study. The introduction presents an overview of recent interdisciplinary research on possession and scholarly attempts at a working definition, followed by a brief outline of the individual case studies in this volume"--
Literaturangaben
Keywords: Spirit possession